Multifaceted Mechanisms of WY-14643 to Stabilize the Blood-Brain Barrier in a Model of Traumatic Brain Injury - Neuhaus, Winfried; Krämer, Tobias; Neuhoff, Anja; Gölz, Christina; Thal, Serge C.; Förster, Carola Y. (Frontiers in Molecular Neuroscience, 2017)
The blood-brain barrier (BBB) is damaged during ischemic insults such as traumatic brain injury or stroke. This contributes to vasogenic edema formation and deteriorate disease outcomes. Enormous efforts are pursued to understand underlying mechanisms of ischemic insults and develop novel therapeutic strategies. In the present study the effects of PPARα agonist WY-14643 were investigated to prevent BBB breakdown and reduce edema formation. WY-14643 inhibited barrier damage in a mouse BBB in vitro model of traumatic brain injury based on oxygen/glucose deprivation in a concentration dependent manner. This was linked to changes of the localization of tight junction proteins. Furthermore, WY-14643 altered phosphorylation of kinases ERK1/2, p38 and SAPK/JNK and was able to inhibit proteosomal activity. Moreover, addition of WY-14643 upregulated PAI-1 leading to decreased t-PA activity. Mouse in vivo experiments showed significantly decreased edema formation in a controlled cortical impact model of traumatic brain injury after WY-14643 application, which was not found in PAI-1 knockout mice. Generally, data suggested that WY-14643 induced cellular responses which were dependent as well as independent from PPARα mediated transcription. In conclusion, novel mechanisms of a PPARα agonist were elucidated to attenuate BBB breakdown during traumatic brain injury in vitro.